Cost-effectiveness of Diabetes Prevention Interventions Targeting High-risk Individuals and Whole Populations: A Systematic Review - Zhou, Xilin; Siegel, Karen R; Ng, Boon Peng; Jawanda, Shawn; Proia, Krista K; Zhang, Xuanping; Albright, Ann L; Zhang, Ping (Diabetes care, 2020)
We conducted a systematic review of studies evaluating the cost-effectiveness (CE) of interventions to prevent type 2 diabetes (T2D) among high-risk individuals and whole populations. Interventions targeting high-risk individuals are those that identify people at high risk of developing T2D and then treat them with either lifestyle or metformin interventions. Population-based prevention strategies are those that focus on the whole population regardless of the level of risk, creating public health impact through policy implementation, campaigns, and other environmental strategies. We systematically searched seven electronic databases for studies published in English between 2008 and 2017. We grouped lifestyle interventions targeting high-risk individuals by delivery method and personnel type. We used the median incremental cost-effectiveness ratio (ICER), measured in cost per quality-adjusted life year (QALY) or cost saved to measure the CE of interventions. We used the $50,000/QALY threshold to determine whether an intervention was cost-effective or not. ICERs are reported in 2017 U.S. dollars. Our review included 39 studies: 28 on interventions targeting high-risk individuals and 11 targeting whole populations. Both lifestyle and metformin interventions in high-risk individuals were cost-effective from a health care system or a societal perspective, with median ICERs of $12,510/QALY and $17,089/QALY, respectively, compared with no intervention. Among lifestyle interventions, those that followed a Diabetes Prevention Program (DPP) curriculum had a median ICER of $6,212/QALY, while those that did not follow a DPP curriculum had a median ICER of $13,228/QALY. Compared with lifestyle interventions delivered one-on-one or by a health professional, those offered in a group setting or provided by a combination of health professionals and lay health workers had lower ICERs. Among population-based interventions, taxing sugar-sweetened beverages was cost-saving from both the health care system and governmental perspectives. Evaluations of other population-based interventions-including fruit and vegetable subsidies, community-based education programs, and modifications to the built environment-showed inconsistent results. Most of the T2D prevention interventions included in our review were found to be either cost-effective or cost-saving. Our findings may help decision makers set priorities and allocate resources for T2D prevention in real-world settings.